(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine the development of Lemo Beach Tourism Place in Burau District, East Luwu Regency. This study used a qualitive approach with a descriptive type. As for the number of informants in the study were 3 people. The data collection technique were interview and documentation. Meanwhile, the data validation techniques used triangulation of sources, techniques and time. Selection of informants based on the views of the authors that the informants had knowledge, and information about the problems the author was thorough. The results showed that the condition of the charm of Lemo Beach was already good, this seen from the very beautiful natural appearance, but there were several problems that arose and it could reduce the selling value of this tourist attraction, among others, namely poorly maintained facilities, which became The main icon of Lemo Beach, the unavailability of sufficient facilities and infrastructure to support the dewelopment of this tourist attraction, the waste problem that had not been resolved at several points of Lemo Beach locations. Keywords: Development, tourist attraction